SEROPREVALENCE OF TOXOPLASMOSIS IN PREGNANT WOMEN IN A CITY IN RIO GRANDE DO NORTE STATE, BRAZIL - Christina Freitas, Laura; Radan de Vasconcelos Marques, Michael; Beatriz de Carvalho Holanda Leite, Ranny; Maria de Carvalho Xavier Holanda, Cecília; Santos de Arruda Barbosa, Vanessa (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Toxoplasmosis is caused by Toxoplasma gondii, which is particularly relevant in pregnant women, due to the risk of congenital infection. The aim of this study was to study the serological pro?leofpregnantwomenandanalyzesomefactorsrelatedtoinfectioninthisgroup.A descriptive and retrospective study was performed analyzing the results of 356 pregnant women in the Mixed Health Unit of Jaçanã-RN from 2009 to 2014. Results of serological tests for IgG and IgM anti-T. gondii antibodies were provided by LACEN-RN. The chi-square test (?2)wascalculatedbeingconsideredstatistically signi?cantforp<0.05.Theresultsshowed that: 59% of the pregnant women tested presented serology IgG anti-T. gondii reagent (IgG+) and IgM anti-T. gondii non-reactive (IgM-), 0.6% reagent for both (IgG+ and IgM+) and 40.4% susceptible to infection(IgG- and IgM-).71.3% of thewomen were testedin the ?rsttrimester of pregnancy; the 20-29 years of age range was the most prevalent (62.5%) and the 11-19 years of age range was the most susceptible (47%). The rural women had the highest incidence of positive serology (60.2%) and those from the urban area were the most susceptible (40.7%). There was no statistical association between serology and the age group (p=0.282) and origin (p=0.881) variables. There is need for investment in prenatal care and health education for the population about toxoplasmosis.